Optimal utilization of gamma camera time in Tc-99m MDP bone scintigraphy - Jawa, Zabah Muhammad (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScMedSc (Medical Imaging and Clinical Oncology. Nuclear Medicine))--University of Stellenbosch, 2007.